Portuguese revolution of 1974–1975 - Fernandes, T. (Encyclopedia of social and political movements, 2023)
The structural reasons that caused the Portuguese revolution of 1974–1975 fit neatly into the general theories of social revolution: an exclusionary and highly repressive regime, riddled with intense elite conflicts, collapsing under severe military and financial pressures, and unexpectedly giving way to a series of autonomous radical and transgressive popular mobilizations and protests. Portugal’s revolution started on 25 April 1974, when a coup by a group of young left-wing middle-rank military officers, the Armed Forces Movement (MFA), deposed the authoritarian New State regime (1933–1974), then dealing with a 13-year-old war in its’ African colonies of Angola, Guinea-Bissau, and Mozambique. The reasons for the coup were at once political and professional. Not only were the professional officers unhappy with the fact that they could be overtaken in promotions by noncareer officers, but they believed victory in the colonial war was impossible. A war with no end in sight, for which the regime had no solution, and professional grievances combined to set off the 1974 coup. In its political program, presented soon after the coup, the MFA defended the establishment of a democratic regime in Portugal.